2017
DOI: 10.1038/s41598-017-17032-7
|View full text |Cite
|
Sign up to set email alerts
|

A chalcohalide glass/alloy based Ag+ ion - selective electrode with nanomolar detection limit

Abstract: In this paper, a silver ion-selective electrode material with lower detection limit is presented. The electrode is based on 22.5As2S3-22.5Ag2S-55AgCl chalcohalide glass membranes. The low detection limit decreases from the micromolar range of the original Ag2S-As2S3 electrode to the nanomolar level (1.89 nM) by introducing AgCl. The addition of AgCl increases the conductivity of the glasses and improves the analytical properties of electrodes because of the joint effects of Ag+ and Cl- on network structure of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(6 citation statements)
references
References 52 publications
0
6
0
Order By: Relevance
“…As declared in Figure 8, the response time of developed graphene sensor decreased gradually from 5, 4 to 3 s as the CLP.HCl concentration increased from 1.0×10 −5 to 1.0×10 −2 mol L −1 . This behavior may be stemmed from the diffusion driving force of the diffusion layer which increases gradually with the analyte concentration increases leading to faster ion transport and so, the sensor displayed shorter response time [52, 53]. Furthermore, the fabricated CLP.HCl selective sensor showed very fast response time of 4 s overall the working concentration range (1.0×10 −5 −1.0×10 −2 mol L −1 ) affirming the superior sensitivity of the developed electrode.…”
Section: Resultsmentioning
confidence: 88%
“…As declared in Figure 8, the response time of developed graphene sensor decreased gradually from 5, 4 to 3 s as the CLP.HCl concentration increased from 1.0×10 −5 to 1.0×10 −2 mol L −1 . This behavior may be stemmed from the diffusion driving force of the diffusion layer which increases gradually with the analyte concentration increases leading to faster ion transport and so, the sensor displayed shorter response time [52, 53]. Furthermore, the fabricated CLP.HCl selective sensor showed very fast response time of 4 s overall the working concentration range (1.0×10 −5 −1.0×10 −2 mol L −1 ) affirming the superior sensitivity of the developed electrode.…”
Section: Resultsmentioning
confidence: 88%
“…Our previous study has found that the Ag + ‐ISEs based on the AgCl‐Ag 2 S‐As 2 S 3 ChH glass system possess a low Ag + detection limit . A following study also shows that these Ag + ‐ISEs also well respond to Cl − ions, thus being potentially useful for determining the chloride ion concentration in aqueous solutions.…”
Section: Introductionmentioning
confidence: 73%
“…Importantly, the operation of one device does not hinder the other devices establishing their operability in both standalone manner and in a multiplexing array. Such an array provides a distinct advantage over other ISE assemblies [44][45][46] that can operate only in stand-alone fashion. Further versatility of the sensor is demonstrated by operating the CNT-thread as a common RE while utilising two different WE for Hg 2+ and Cd 2+ within the same sensor (Figure 4(k)).…”
Section: Resultsmentioning
confidence: 99%